Usefulness of bone microarchitectural and geometric DXA‐derived parameters in haemophilic patients. Issue 6 (1st October 2018) - Ulivieri, Fabio Massimo; Rebagliati, Giulia Antonella Angela; Piodi, Luca Petruccio; Solimeno, Luigi Piero; Pasta, Gianluigi; Boccalandro, Elena; Fasulo, Maria Rosaria; Mancuso, Maria Elisa; Santagostino, Elena
Abstract: Introduction: Haemophilia is a recessive X‐linked inherited bleeding disorder, whose typical symptom is spontaneous intra‐articular haemorrhage leading to joint damage, which can be quantified by the Haemophilia Joint Health Score (HJHS). Arthropathy and other characteristics of haemophilic patients may reduce bone mineral density (BMD), increasing the risk for fragility fractures, which also may occur due to bone quality impairment. Aim: To evaluate bone quantity by BMD and bone quality by Trabecular Bone Score (TBS), bone strain (BS) and hip structural analysis (HSA) in a haemophilic population, and to relate these parameters to general and specific risk factors for osteoporosis and to HJHS. Methods: Seventy haemophilic patients ≥18 years were enrolled. Densitometric derived lumbar spine and femoral BMD with TBS, BS and HSA were performed. Data regarding risk factors for osteoporosis, presence of arthroprosthesis or arthrodesis were collected, and HJHS was calculated. A Z‐score ≤−2.0 defined a low bone mass. Results: Overall, a reduced bone mass was present in 52 patients at the femur and in 38 at the lumbar spine. Lumbar spine BMD, TBS and BS did not correlate with HJHS. HSA bone geometric parameters correlated negatively with HJHS. BMD and HSA correlated with some risk factors for osteoporosis, namely HIV and its therapy, hepatitis C and smoking. Conclusions: Haemophilic patients showed a reduced BMD at lumbar spine and/or femur. Femoral bone density and geometry correlated with HJHS. The microarchitecture of the trabecular vertebral bone seemed to be not influenced by the haemophilic joint damage.